EVALUATION OF TECHNICAL AND ECONOMIC ASPECTS OF REPLACING MECHANICAL TRANSPORT WITH PNEUMATIC - Oluški, Nikola; Bukurov, Maša; Živkov, Andreja; Popović, Petar; Vukić, Marko (Journal on Processing and Energy in Agriculture, 2024)
This paper explores the cost-effectiveness of pneumatic transport of wheat compared to mechanical transport on agricultural premises. A comparison was made with the existing mechanical transporter at the "Aleksić" agricultural farm in Novi Slankamen. The chosen method, flying pneumatic transport, underwent experimental capacity determination using volumetric methods for pneumatic transport calculations. With an initial wheat mass flow of 4.8 kg/s, calculations aimed to ascertain the motor power required to operate the blower, factoring in pressure drop in the pipeline. Results indicated a 4230 Pa pressure drop and a 2.12 kW blower motor power. Economic analysis revealed less favorable outcomes, with a payback period of 10500 working hours or 436 days due to seasonal transportation needs. Performance analysis suggested over 6000 trailers would be required for investment repayment. Notably, the analysis solely focused on wheat transport, overlooking potential for service work or modern pneumatic transport solutions, underscoring the necessity for further research for more relevant conclusions.